Detection and phylogenetic classification of Neoehrlichia mikurensis in rodents from the region of Liupan Mountain, China - Wang, Xiaodong; Pang, Bo; Kou, Zengqiang; Zhao, Jiaqi; Yan, Yi; Chen, Tan; Yang, Liping (Frontiers in Microbiology, 2024)
Neoehrlichia mikurensis (N. mikurensis) is an emerging tick-borne pathogen that can cause neoehrlichiosis. Rodents are considered the major host for N. mikurensis. Currently, N. mikurensis has been detected in rodents in several studies from China and other countries. However, no research on N. mikurensis infection in rodents has been reported in the Liupan mountain region. The region of Liupan Mountain, located in northwestern China, is the center of the triangle formed by the cities of Xi’an, Yinchuan, and Lanzhou, with multiple tourist sites in the region. To survey whether there is N. mikurensis in hosts, rodents were captured in this region in September 2020. A nested polymerase chain reaction was used to detect the DNA of N. mikurensis, followed by nucleotide sequencing and phylogenetic analysis. In the region, among 88 rodents, 3 rodents were detected positive for N. mikurensis, a detection rate of 3.4%. Based on phylogenetic analysis of the partial groEL gene sequences, N. mikurensis from rodents in Liupan Mountain clustered in the same evolutionary branch with those found in rodents from Japan, Russia, and northeastern China, and also in ticks and clinical cases from Heilongjiang Province in northeastern China.